Antihyperurisemia activity of water extract of black seed (Coleus ambonicusLour) in balb-c mice and its standardization - Andi Suhendi; Nurcahyanti .; Muhtadi .; EM Sutrisna (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Effect of water extract of black seed on uric acid metabolism in hyperuricemia mice models were studied. The influence of water extract of black seed on uric acid biosynthesis was xamined using mice treated by 250 mg/ body weight potassium oxonate intra peritoneal. The result showed that water extract of black seed (200 mg/kg body weight, per oral) have a significant effect in reduction in plasma uric acid levels in comparison to negative control, but less active than positive control (allopurinol). The levels of uric acid in mice plasma for negative control, black seed extract and positive control were 3.100 ± 0.346 mg/dL, 0.200 ± 0.100 mg/dL dan 1.200 ± 0.561 mg/dL, respectively. The standardization performed by determined specific and non specific parameters based on National Bureau of Food and Drug, Republic of Indonesia. Specific parameters of water extract of black seed are phenolic content, and flavonoid content are 0.664 ± 0.035 % and 0.400 ± 0.018 %, respectively. Non specific parameters of water extract of black seed are loss of weight, water content, ash content, ash insoluble acid content, heavy metals contamination (Pb and Cd), and aflatoxin residue are 14.93-14.99%, 6.09-7.89%, 7.12-7.49%, 5.20-6.66%, 6.405 +0.211 ppm, 0.0096 +0, not detected, respectively.Key words: antihyperuricemia effect, water extract of black seed, standardization